Dinâmica da água em diásporos de espécies de interesse agrícola - Oliveira, João Paulo Ribeiro de (2015)
Consecrated as imbibition curve, the dynamics of water absorption demonstrates diaspore germination in a reliable way. Nevertheless, this event still is little explored and even neglected. Moreover, if the dynamics of water demonstrates the germination of a diaspore, wouldn\'t it be interesting to measure it? Before even thinking about measuring this process, there is a need to standardize the size of the sample to study it. There are large sampling fluctuations in studies demonstrating the dynamics of water in diaspores. Thinking about it, this thesis presents three chapters dedicated to the study of the dynamics of water in diaspores. Chapter I makes a theoretical approach of this process and demonstrates the misuse of the term imbibition to name the curve which shows the dynamics of water in diaspores; Chapter II presents optimum sample size to analyze the dynamic process; Chapter III provides dynamic measures capable of accurately quantifying the process, through rate (speed), proposing a rereading of the phases of germination stricto sensu. To this purpose, diaspores belonging to three lots with distinct qualities of five species of great agricultural significance were used. These diaspores (n = 50) were placed in contact with water and weighed, every hour, until, at least, one embryo protrusion had occurred in each sample of each lot. Data of mass collected were used to measure the optimum sample size, as well as to calculate the various measures of the process (initial diffusion coefficient, entropy, uniformity, speed and acceleration of water absorption for diaspores). The weighted mass increment curves showed that germination occurs in a similar manner, independent of the physiological quality of the batch or of the species under study. The Modified Maximum Curvature Method (MMCM) is an appropriate method for measuring the variability of the water dynamic on diaspores of most species and, therefore, obtain the size of sample for the analysis of this process. In general, seven diaspores are needed to study the process. Measures of the water dynamic on diaspores are viable for inferences of germination stricto sensu. Among the measures, the rate of water dynamics (speed) demonstrates various metabolic phases of germination. Finally, the germinal process is not triphase, but polyphase and, in a specific point, with varietal traits.